A pan-crop metagenomic exploration of microbial communities linked to pesticide and xenobiotic degradation pathways in agricultural microbiomes - Ratna Prabha; Mahesh K. Samota; M. K. Verma; Shailendra Gupta; Anil Rai; S. C. Dubey; D. P. Singh (Discover Agriculture)
Abstract Microbes inhabiting rhizosphere and soils of close vicinity of plants play a pivotal role in plant growth promotion, enhance plant fitness, and improve soil fertility through the cycling of different nutrients like carbon, nitrogen, sulphur etc. The study of rhizosphere and soil-associated microbiome can enhance our knowledge about different genes (known and novel, both) and pathways associated with various metabolic activities of immense importance. Current agricultural system is heavily dependent on numerous synthetic chemicals like insecticides, fungicides, and herbicides. Regular application of such chemicals has raised the issues of environmental pollution and imposed severe risks on human beings. With extensive research, microbes are now established as the most important means of pesticide degradation. The current study focuses on the identification of different genes and pathways involved in the degradation and remediation of various xenobiotics and their components in the 105 different metagenome and metatranscriptome samples of rhizosphere or associated soil of seven different crops, i.e. wheat, oat, pea, soybean, sugarcane, kodo and common bean. For different kinds of xenobiotics components, biodegradation and associated metabolism were analyzed and numerous gene and enzymes associated with these processes were identified. Statistical and computational analyses revealed several significant pathways, including benzoate degradation, central meta-cleavage pathway, salicylate and gentisate catabolism, and phenylacetyl-CoA catabolic pathway. Identified genes/enzymes are important for degradation of various xenobiotic including constituents of different pesticides. To facilitate access to this information, the researchers developed XenMetaDB, a comprehensive online database cataloging all identified enzymes and pathways, accessible at http://webapp.cabgrid.res.in/xenmetadb/ . Identification of xenobiotics degradating enzymes, genes and their further utilization for bioremediation purposes is an important aspect for near future. Findings of current study will provide background for future research over application of microorganisms for bioremediation and biodegradation activities.